Phase transitions in the Cu-Sb-S system - M. H. Braga (2008)
The aim of this study is to determine the thermodynamic influence of the presence of Cu3SbS3, Cu2S and Sb2S3 in the formation of Cu12Sb4S13 - equivalent to mineral tetrahedrite. Thus, the Cu-Sb-S system is studied. Twenty three samples, with compositions that essentially lay along the vertical section Cu2S-Sb2S3, were prepared. The samples were analyzed by Electron Microprobe (EPMA) in order to determine the room temperature phases' composition. Samples were also analyzed by Differential Thermal Analysis (DTA/DSC) in order to establish thermal transitions, and by X-Ray Diffraction (XRD), at room and high temperatures, so as to determine the phases that are present in the equilibria at certain temperatures. The experimental phase diagram was established and the results were compared with those available in the literature.